KEPEMIMPINAN TRANSFORMASIONAL-SPIRITUAL DALAM MANAJEMEN PENDIDIKAN ISLAM - Istikhori; Nisa Putri Wulandari; E. Komarudin; Venti Fatmawati Suhendra; Muhammad Atep Saepul Rahman; Ridwan Hermawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Basic education in the modern era faces a dual challenge of improving learning quality while strengthening character education from an early age. In this context, school leadership plays a crucial role in shaping policy direction, learning climate, and value internalization. However, leadership practices in many primary schools remain largely administrative and have not systematically integrated moral and spiritual dimensions. This study aims to conceptually examine the role of transformational–spiritual leadership in managing basic education to support the development of excellent and character-based schools. This study employed a qualitative approach using library research. Data were collected through a critical review and synthesis of relevant literature on transformational leadership, spiritual leadership, educational management, and character education. Data were analyzed using content analysis and thematic analysis to identify key patterns and conceptual relationships. The findings indicate that transformational leadership enriched with spiritual values contributes significantly to creating a school climate conducive to meaningful learning and character development in primary education. Such leadership strengthens role modeling, value-based vision, and teachers’ roles as key agents of character education. In addition, value-based educational human resource management functions as an operational mechanism that translates leadership vision into daily instructional practices. A consistent and value-oriented school culture also mediates and sustains the impact of leadership on students’ character formation. These findings highlight transformational–spiritual leadership as an essential foundation for balancing academic quality and character development in basic education.